Team creativity and innovation - Reiter-Palmon, Roni, 1964- (New York, NY : Oxford University Press, 2018)
"For the past two decades, creativity and innovation have been viewed by researchers as critical to organizational success and survival. Understanding the factors that facilitate or inhibit creativity and innovation at the individual level has been the focus of much of the research in this area. However, while earlier work on teams considered the working dynamics of the group as a context variable with individual creativity the outcome, research now emphasizes group creativity as the intended, desired outcome. This shift in thought has occurred because many of the problems routinely facing organizations are complex and cannot be solved by a single individual at the helm. Edited by Roni Reiter-Palmon, Team Creativity and Innovation provides readers with a state-of-the-art review of the major concepts and current research related to the demonstrable benefits of team creativity and innovation. In this volume, Reiter-Palmon and contributors explore such topics as team collaboration and communication, trust and psychological safety, team diversity, social networks, conflict, organizational learning, and more as a way to introduce readers to the issues that matter most in today's modern, forward-thinking workplace."--
"For the past two decades, creativity and innovation have been viewed by researchers as critical to organizational success and survival. The purpose of this edited book is to provide a state-of-the-art review of the major concepts, current research, and practice issues related to team creativity and innovation"--
Part I: Introduction -- Chapter 1: Team Creativity and Innovation: Importance and Directions / Roni Reiter-Palmon and Mackenzie Harms -- Chapter 2: Overview of Team Creativity and Innovation / Paul B. Paulus and Jared B. Kenworthy -- Part II: Team Processes -- Chapter 3: Team Diversity and Team Creativity: A Categorization-Elaboration Perspective / Daan van Knippenberg and Inga J. Hoever -- Chapter 4: Team Creativity: Cognitive Processes Underlying Problem-Solving / Mackenzie Harms, Victoria Kennel, and Roni Reiter-Palmon -- Chapter 5: Social Processes and Team Creativity: Locating Collective Creativity in Team Interactions / Sarah Harvey and Chia-yu Kou -- Part III: Organizational Factors and Levels -- Chapter 6: Leader Impacts on Creative Teams: Direction, Engagement, and Sales / Michael D. Mumford, Tyler Mulhearn, Logan L. Watts, Logan M. Steele, and Tristan McIntosh -- Chapter 7: 20 Years Later: Organizational Context for Team Creativity / Christina E. Shalley, Robert C. Lichtfield, and Lucy L. Gilson -- Chapter 8: A Multi-level Model of Collaboration and Creativity / Michael Beyerlein, Crystal Han, and Ambika Prasad -- Chapter 9: Creativity and Innovation in Multiteam Systems / Stephen J. Zaccaro, Laura S. Fletcher, and Leslie A. DeChurch -- Part IV: Applications -- Chapter 10: Selection and Team Creativity: Meeting Unique Challenges Through Diversity and Flexibility / Samuel T. Hunter, Brett H. Neely, and Melissa B. Gutworth -- Chapter 11: Training Creativity in Teams / Shannon L. Marlow, Christina N. Lacerenza, Amanda L. Woods, and Eduardo Salas -- Chapter 12: Team Innovation in Healthcare / Victoria Kennel, Katherine Jones, and Roni Reiter-Palmon -- Chapter 13: Destruction through Collaboration: How Terrorists Work Together Toward Malevolent Innovation / Gina Scott Ligon, Douglas C. Derrick, and Mackenzie Harms.
Includes bibliographical references and index.
Keywords: Creative ability in business; Teams in the workplace; Organizational behavior; Psychology -- Industrial & Organizational Psychology; BUSINESS & ECONOMICS -- Organizational Behavior